A Practical Update on Pediatric Eosinophilic Esophagitis - Martina Votto; Maria De Filippo; Silvia Caimmi; Cristiana Indolfi; Alessandro Raffaele; Maria Angela Tosca; Gian Luigi Marseglia; Amelia Licari (Children, 2023)
Eosinophilic esophagitis (EoE) is an emerging atopic disease of unknown etiology limited to the esophagus. The pathogenesis is still understood and is likely characterized by type 2 inflammation. Food allergens are the primary triggers of EoE that stimulate inflammatory cells through an impaired esophageal barrier. In children and adolescents, clinical presentation varies with age and mainly includes food refusal, recurrent vomiting, failure to thrive, abdominal/epigastric pain, dysphagia, and food impaction. Upper-gastrointestinal endoscopy is the gold standard for diagnosing and monitoring EoE. EoE therapy aims to achieve clinical, endoscopic, and histological (“deep”) remission; prevent esophageal fibrosis; and improve quality of life. In pediatrics, the cornerstones of therapy are proton pump inhibitors, topical steroids (swallowed fluticasone and viscous budesonide), and food elimination diets. In recent years, much progress has been made in understanding EoE pathogenesis, characterizing the clinical and molecular heterogeneity, and identifying new therapeutic approaches. Notably, clinical, molecular, endoscopic, and histological features reflect and influence the evolution of inflammation over time and the response to currently available treatments. Therefore, different EoE phenotypes and endotypes have recently been recognized. Dupilumab recently was approved by FDA and EMA as the first biological therapy for adolescents (≥12 years) and adults with active EoE, but other biologics are still under consideration. Due to its chronic course, EoE management requires long-term therapy, a multidisciplinary approach, and regular follow-ups.